The Role of Performance in Mediating the Effect of Creativity and Motivation on Well-Being of Gentongan Batik Crafters (Study on Crafters in Bangkalan Regency) - Zakiyyatul Fitri Ilmiyah; Hasanah, Uswatun (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines performance as a mediator of the effects of creativity and motivation on the well-being of gentongan batik artisans in Bangkalan. Using a quantitative survey of 170 artisans and PLS-SEM analysis, results show that creativity and motivation positively and significantly affect performance, which in turn enhances well-being. Performance also mediates the relationship between creativity, motivation, and well-being. These findings highlight the critical role of psychological and work-related factors in artisan welfare. The study contributes to the performance-based well-being model and offers practical insights for stakeholders to foster creativity, skills, and sustainable support in artisan communities.Keyword: Creativity; Motivation; Performance; Well-Being; Gentongan Batik